2017
DOI: 10.1177/0144598717748762
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic characterization of cracking and hydrolysis of n-pentane and n-octadecane at 300–375℃ with geological implications

Abstract: Hydrous and anhydrous isothermal experiments on n-pentane and n-octadecane were conducted at 300-375 C for durations up to 1094 h to evaluate the cracking and hydrolysis of hydrocarbons, using fused silica capillary capsules as micro-reactors. The chemical compositions of the gaseous products during cracking of n-octadecane at 350 and 375 C were methane, ethane, propane, and n-butane. The aqueous product in the hydrolysis of n-pentane and n-octadecane at 300-375 C was alcohol. Alkenes and hydrogen were not det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The gas released over this temperature range for C8AB was analyzed by μGC/MS. The MS results are not reported, but we can mention that, like for alkanes, [49][50][51][52] a number of cracking products (saturated and unsaturated C 1 to C 7 hydrocarbons) were detected above 250°C.…”
Section: Thermal Analyses Of the Cxabmentioning
confidence: 99%
“…The gas released over this temperature range for C8AB was analyzed by μGC/MS. The MS results are not reported, but we can mention that, like for alkanes, [49][50][51][52] a number of cracking products (saturated and unsaturated C 1 to C 7 hydrocarbons) were detected above 250°C.…”
Section: Thermal Analyses Of the Cxabmentioning
confidence: 99%
“…The increase in the yields of H 2 and CO 2 in hydrothermal conditions should be attributed to the water–hydrocarbon reactions (Lewan, 1997; Seewald, 2003). These results demonstrate that water should provide O and H for gas generation in our pyrolysis (He et al., 2018a; Leif and Simoneit, 2000; Seewald, 2003; Wang et al., 2017).…”
Section: Resultsmentioning
confidence: 59%
“…Water was suggested to affect and even participate in the petroleum generation from organic matters (Helgeson et al, 1993;Lewan et al, 1979;Lewan, 1997;Seewald, 2003, Seewald et al, 2000. Till now, numerous hydrous or hydrothermal experiments have been conducted to understand the effects of water on oil and gas generation (Behar et al, 2003;Gao et al, 2014;He et al, 2018a;Lewan et al, 1979;Lewan, 1997;Lewan and Roy, 2011;Pan et al, 2009;Wang et al, 2017). These works observed that water can provide hydrogen and oxygen for hydrocarbon generation, and alter the features of individual products as well as acting as a medium for petroleum expulsion from source rocks (Hoering, 1984;Lewan, 1997;Schimmelmann et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, with increasing burial depth, gypsum-bearing rocks and limestone are preserved, whereas dolomite is more rapidly dissolved. Wang et al (2018) conduct hydrous and anhydrous isothermal experiments on n-pentanes and n-octadecanes to evaluate the cracking and hydrolysis of hydrocarbons. Gases produced during cracking of n-octadecane at 350 C and 375 C contain methane, ethane, propane, and n-butane.…”
Section: General Methodologies Applied To Petroliferous Basins In Wesmentioning
confidence: 99%